2018
DOI: 10.1044/2018_jslhr-l-17-0363
|View full text |Cite
|
Sign up to set email alerts
|

An Eye-Tracking Study of Receptive Verb Knowledge in Toddlers

Abstract: Purpose We examined receptive verb knowledge in 22- to 24-month-old toddlers with a dynamic video eye-tracking test. The primary goal of the study was to examine the utility of eye-gaze measures that are commonly used to study noun knowledge for studying verb knowledge. Method Forty typically developing toddlers participated. They viewed 2 videos side by side (e.g., girl clapping, same girl stretching) and were asked to find one of them (e.g., “Where is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 78 publications
5
48
0
Order By: Relevance
“…We know less about how eye gaze measures of lexical processing with dynamic scenes are related to outcomes. A handful of studies have used dynamic scenes to depict verb referents in eye-tracking tasks with young children (Bergelson & Swingley, 2013;Goldfield, Gencarella, & Fornari, 2016;Golinkoff et al, 1987;Horvath, 2019;Horvath & Arunachalam, in preparation;Huttenlocher, Smiley, & Charney, 1983;Naigles, 1997;Naigles & Hoff, 2006;Valleau et al, 2018). Related to the current study, Goldfield et al (2016) found that eye gaze measures of verb knowledge correlated with PPVT scores in children ages 3 to 5 years (they did not examine lexical processing speed specifically).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…We know less about how eye gaze measures of lexical processing with dynamic scenes are related to outcomes. A handful of studies have used dynamic scenes to depict verb referents in eye-tracking tasks with young children (Bergelson & Swingley, 2013;Goldfield, Gencarella, & Fornari, 2016;Golinkoff et al, 1987;Horvath, 2019;Horvath & Arunachalam, in preparation;Huttenlocher, Smiley, & Charney, 1983;Naigles, 1997;Naigles & Hoff, 2006;Valleau et al, 2018). Related to the current study, Goldfield et al (2016) found that eye gaze measures of verb knowledge correlated with PPVT scores in children ages 3 to 5 years (they did not examine lexical processing speed specifically).…”
mentioning
confidence: 56%
“…Related to the current study, Goldfield et al (2016) found that eye gaze measures of verb knowledge correlated with PPVT scores in children ages 3 to 5 years (they did not examine lexical processing speed specifically). In contrast, Valleau et al (2018) found that lexical processing speed for verbs did not correlate with expressive vocabulary for 22-to 23-month-olds -though it did for nouns, just as in prior work (e.g., Fernald et al, 2006). However, in a study of older children with autism spectrum disorder in the same paradigm as Valleau et al (2018), latency did correlate with vocabulary for both nouns and verbs (Horvath, 2019;Horvath & Arunachalam, in preparation).…”
mentioning
confidence: 74%
See 3 more Smart Citations